2014
DOI: 10.1128/jb.01758-14
|View full text |Cite
|
Sign up to set email alerts
|

Control of Natural Transformation in Salivarius Streptococci through Specific Degradation of σ X by the MecA-ClpCP Protease Complex

Abstract: cCompetence for natural DNA transformation is a tightly controlled developmental process in streptococci. In mutans and salivarius species, the abundance of the central competence regulator X is regulated at two levels: transcriptional, by the ComRS signaling system via the X /ComX/SigX-inducing peptide (XIP), and posttranscriptional, by the adaptor protein MecA and its associated Clp ATPase, ClpC. In this study, we further investigated the mechanism and function of the MecA-ClpC control system in the salivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 41 publications
(126 reference statements)
4
36
0
Order By: Relevance
“…This is important, since MecA is ubiquitous among streptococci and its homologs are found in the complete genomes of all species sequenced so far [34,35]. In a most recent study, Wahl et al have provided convincing in vitro evidence that confirms the importance of MecA-ClpCP complex in the posttranslational regulation of SigX in S. thermophilus [40]. However, their work has not described how MecA is regulated in vivo under test growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This is important, since MecA is ubiquitous among streptococci and its homologs are found in the complete genomes of all species sequenced so far [34,35]. In a most recent study, Wahl et al have provided convincing in vitro evidence that confirms the importance of MecA-ClpCP complex in the posttranslational regulation of SigX in S. thermophilus [40]. However, their work has not described how MecA is regulated in vivo under test growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In streptococci, competence is a transient physiological bacterial state (Seaton et al, 2011, 2015; Desai et al, 2012; Federle and Morrison, 2012; Guo et al, 2014) and the mechanisms mediating shut-down have only been partially elucidated in some species (Boutry et al, 2012; Tian et al, 2013; Weng et al, 2013; Dong et al, 2014; Wahl et al, 2014). In S. pneumoniae , which possess the ComCDE competence regulatory system, the exit from competence is regulated by multiple ComX dependent- and independent mechanisms (Chastanet et al, 2001; Bergé et al, 2003; Mortier-Barrière et al, 2007; Piotrowski et al, 2009; Martin et al, 2013; Mirouze et al, 2013; Weng et al, 2013) In S. mutans and S. thermophilus which both utilize the ComRS system to regulate competence development, MecA negatively regulates competence development by targeting the ClpC-ClpP protease activity to ComX (Boutry et al, 2012; Tian et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In S. pneumoniae , which possess the ComCDE competence regulatory system, the exit from competence is regulated by multiple ComX dependent- and independent mechanisms (Chastanet et al, 2001; Bergé et al, 2003; Mortier-Barrière et al, 2007; Piotrowski et al, 2009; Martin et al, 2013; Mirouze et al, 2013; Weng et al, 2013) In S. mutans and S. thermophilus which both utilize the ComRS system to regulate competence development, MecA negatively regulates competence development by targeting the ClpC-ClpP protease activity to ComX (Boutry et al, 2012; Tian et al, 2013). Moreover, in vitro degradation of ComX by ClpC-ClpP was shown to be strictly dependent on MecA (Wahl et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic characterization of an S. thermophilus clpC mutant revealed that ClpC plays a role in the development of genetic competence in this organism (310). The alternative sigma factor ComX, which drives the expression of competence genes, was shown in S. thermophilus and S. mutans to be under posttranslational regulation by ClpCP through active degradation (310)(311)(312)(313). This task is performed by ClpEP in S. pneumoniae (314).…”
Section: Treating Damaged Macromoleculesmentioning
confidence: 99%